2020
DOI: 10.1111/ajgw.12431
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary sensory characterisation of the diverse astringency of single cultivar Italian red wines and correlation of sub‐qualities with chemical composition

Abstract: Background and Aims: Italy is the richest grape-producing country in terms of cultivars. Our aims were to describe the diversity of astringency of Italian red wines from 11 cultivars, Teroldego, Corvina, Raboso, Nebbiolo, Sangiovese, Sagrantino, Montepulciano, Cannonau, Aglianico, Primitivo and Nerello, and to test correlations between in-mouth sensory variables and chemical composition. Methods and Results: A sample subset was selected by sorting and then assessed on astringency sub-qualities (drying, harsh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 56 publications
(82 reference statements)
1
38
0
Order By: Relevance
“…The basic oenological information for the wines is provided in Table S1 and Figure S1 of the Supporting Information. The mid-infrared spectroscopy data can be found in the study by Parpinello et al, 25 and the sensorial analysis data can be found in the study by Piombino et al 26 Winemaking was carried out by each winery independently and according to their standard production practices. However, for each wine, the following specifications were followed: (a) the wines had to be obtained from a single grape variety; (b) the wines had to be fermented in stainless-steel vats; (c) fermentation had to be performed on an industrial scale; (d) sampling was to be performed before malolactic fermentation; (e) wines must not have any contact with oak; (f) 50 mg/L of free SO 2 had to be added at the time of sampling, before bottling in dark glass bottles; and (g) Nomacorc Select Bio 500 (Nomacorc, France) closures had to be used.…”
Section: Methodsmentioning
confidence: 99%
“…The basic oenological information for the wines is provided in Table S1 and Figure S1 of the Supporting Information. The mid-infrared spectroscopy data can be found in the study by Parpinello et al, 25 and the sensorial analysis data can be found in the study by Piombino et al 26 Winemaking was carried out by each winery independently and according to their standard production practices. However, for each wine, the following specifications were followed: (a) the wines had to be obtained from a single grape variety; (b) the wines had to be fermented in stainless-steel vats; (c) fermentation had to be performed on an industrial scale; (d) sampling was to be performed before malolactic fermentation; (e) wines must not have any contact with oak; (f) 50 mg/L of free SO 2 had to be added at the time of sampling, before bottling in dark glass bottles; and (g) Nomacorc Select Bio 500 (Nomacorc, France) closures had to be used.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, our results could somehow explain the “dry,” “harsh” and “dynamic” astringent character, as well as the bitterness of Sagrantino wines [ 36 , 37 ]. The mDP value is only one of the parameters that is able to explain the influence of proanthocyanidins in wine sensorial character.…”
Section: Discussionmentioning
confidence: 87%
“…While the chemical role of the proanthocyanidins is shared by all the red wines, it has emerged that there is a huge diversity in the concentration of these compounds in the grapes from different cultivars [ 20 , 32 , 33 , 34 ]. It is expected that both the differences in the concentration, as well as in the structure, of the tannins can contribute to the huge diversity in the astringency of wines produced from them [ 35 , 36 , 37 ]. The need to build reliable reference values for the composition of each cultivar, to be used in the quality control, and combined with other data, especially the sensory data, calls for the need for accurate measurement via the phloroglucinolysis assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In red wines, colour and "in-mouth" features strongly influence the sensory perception of quality (Peynaud, 1987;Parpinello et al, 2009, Piombino et al, 2020. These characteristics are mainly connected to the polyphenols extracted from black grapes.…”
Section: Introductionmentioning
confidence: 99%